Nicolas, Where Have You Been? - Lionni, Leo 1910-1999. (New York : Alfred A. Knopf, 2007)
Mishap turns to adventure as a young mouse learns that all birds aren't the enemies he thought they were.
"A Borzoi book"--T.p. verso.
Keywords: Birds -- Fiction; Mice -- Fiction